Metabonomic Characteristics of Myocardial Diastolic Dysfunction in Type 2 Diabetic Cardiomyopathy Patients - Hao, Mingyu; Deng, Jianxin; Huang, Xiaohong; Li, Haiyan; Ou, Huiting; Cai, Xiangsheng; She, Jiajie; Liu, Xueting; Chen, Ling; Chen, Shujuan; Liu, Wenlan; Yan, Dewen (Frontiers in Physiology, 2022)
Diabetic cardiomyopathy (DCM) is one of the most important cardiovascular complications in diabetic patients associated with glucose and lipid metabolism disorder, fibrosis, oxidative stress, and inflammation in cardiomyocytes. Despite increasing researches on the molecular pathogenesis of DCM, we are still unclear about metabolic pathways and alterations probably involved in the development of DCM. This study aims to characterize the metabolites of DCM, to identify the relationship between metabolites and biological processes or biological states through untargeted metabolic histology. We have used untargeted metabolomics using UHPLC-MS/MS analyses to profile plasma metabolite from 78 patients with diabetes (39 diabetes with DCM and 39 diabetes without DCM as controls). A total of 84 biochemicals were detected. Comparing to DM patients, 78 differential metabolites in the positive ion mode were identified in DCM patients, including 33 up-regulated and 45 down-regulated differential metabolites; however, there were only 6 differential metabolites identified in the negative mode, including 4 up-regulated and 2 down-regulated differential metabolites. Alterations of several serum metabolite concentrations, belonging to lipids and lipid-like molecules, organic acids and derivatives, organic oxygen compounds, benzenoids, phenylpropanoids and polyketides, and organoheterocyclic compounds, were associated with the development of DCM. KEGG enrichment analysis showed that there are 3 signaling pathways (metabolic pathways, porphyrin and chlorophyll metabolism and lysine degradation) were changed both in negative and positive ion mode. These results demonstrated that differential metabolites and lipids have certain effects on DCM, and its progression to HFpEF, which may improve the prognosis of patients. The metabolites identified here may provide clues for clinical management and the development of effective drugs.